Where Does It Hurt? A Poetic Holding of Existential Hurt - Frattura, Addyson (Art/Research International, 2022)
The question of an existential experience of hurt is not only relevant during present times of enduring hurt through realities such as a deadly pandemic, racialized violence, precarious educational realities, and ongoing struggles for justice in its many forms. The work of this poetic inquiry is enduringly relevant insofar as both institutions and people hold, create, sustain, and attempt to respond to hurt of many kinds. At times, we may cause more hurt than we soothe. As I write, I am grounded in the practices of poetic and literary analysis and position this piece a space and a form to hold the seemingly incommensurable questions for us as teachers, as artists, and as humans existing and living through a world of hurt. As a philosopher of education, I am perpetually concerned with the possibilities of a humanizing education that may soothe and eradicate existential hurt. I look toward poetry and art to show us the way.